PERFORMANCE INDICATORS OF RATIONAL DRUG THERAPY WITH A COMBINATION OF CORONARY HEART DISEASE AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Абдуллаев В. А.; Бахшаліев А. Б.; Юсіфов Р. Н. (World of Medicine and Biology, 2015)
The aim of the study was to examine the effectiveness of rational drug therapy with β-blockers a combination of coronary heart disease and chronic obstructive pulmonary disease. Methods. Conducted a study of the effect of prolonged use of selective β- blockers nebivolol at the same time of day, with liquid, squeezed enough water during or after meals - 5 mg 1 time per day. We studied 58 patients (COPD+CHD - 32 patients, CHD - 26 patients), a leading pathology among whom were ischemic heart disease, demonstrate by angina and/or arrhythmia. In all patients the diagnosis of CHD was confirmed by instrumental studies, stress ECHO, ECG monitoring; biochemical studies of total cholesterol, triglycerides, LDL and HDL. The presence of COPD was diagnosed on the basis of survey data, medical history, physical and instrumental examination - x-ray examination of chest organs, respiratory function, analysis of blood gases and blood oxygen saturation, General and biochemical blood tests, sputum examination. All the patients had history of Smoking was estimated on the basis of who proposed indicators: the index of the smoker and the number of packs/years. Results. Chronotropic efficacy of nebivolol was never in doubt. Selected doses were sufficient to achieve the target heart rate and reduced resting heart rate at 11.25±9,97 beats/min and under a load. Maximum heart rate during symptom-limited samples during therapy was less 15,58±9,15 BPM is Not statistically significant drug effect on bronchial patency: FEV1 was 2,09±0,98 ml before treatment and 2,59±1,14 ml in the process. Conclusions. Monotherapy by nebivolol helps to normalize blood pressure in most patients with hypertensive disease of the 1st and 2nd degree. Nebivolol does not cause orthostatic hypotension, disturbances of lipid and carbohydrate metabolism, does not affect the performance of the functions of external respiration, including in patients with COPD.